Peran Perempuan Pesisir Dalam Mendukung Ekonomi Keluarga Nelayan: Studi di Malabero, Teluk Segara, Bengkulu - Sabilla, Devikha Putri; Heriyanti, Lesti; Djakfar, Ledyawati (Jurnal Community, 2024)
This study examines the role of women in supporting the economic wellbeing of fisher families in Malabero, Segara Bay, Bengkulu City. The focus is on women's contributions to coastal economic activities such as seafood processing, trade, and financial management. The theory used in this research is Talcott Parsons' Structural Functionalism theory with the AGIL framework (Adaptation, Goal Attainment, Integration, and Latency). The AGIL theoretical framework outlines the role of women in the family economy to maintain the balance of the family system and ensure its smooth functioning, particularly the economic functions that cannot be fully performed by the husband as the head of the household.The research method used is qualitative, involving in-depth interviews with women actively participating in household economic activities in fishing communities, as well as employing data analysis techniques such as data reduction, data presentation, and drawing conclusions. The findings show that women in the Malabero coastal area play a crucial role in supporting the economic stability of fisher families. In addition to performing domestic duties as housewives, they are also involved in side businesses. This dual role not only increases family income but also maintains the social and economic stability of the fisher family.Women's empowerment has proven to be important in strengthening the economic resilience and well-being of fisher families along the coast, creating a more independent and competitive society. This study also highlights the need for further government support to enhance the capacity of coastal women in managing family fisheries economically and to strengthen their networks and access to the resources needed. As a result, the role of women in improving the income and welfare of fisher families in Malabero can be more optimal and sustainable.